2014
DOI: 10.1177/1528083714538684
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced functional properties of cotton fabrics using TiO2/SiO2 nanocomposites

Abstract: Anatase titania (TiO 2 ) nanoparticles were prepared from natural minerals (rutile sand) using acid extraction by sol-gel method. The obtained X-ray diffraction results show that the particle possesses crystallite size of 12 nm. The colloidal silica and TiO 2 nanoparticle-embedded colloidal silica solutions were prepared using sol-gel method followed by sonication process. The particle size was measured for the prepared colloidal TiO 2 /SiO 2 sol. The prepared solution was coated on the surface of the cotton f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…The study concluded that the hybrid TiO 2 /SiO 2 nanoparticlecoated fabrics show improved multifunctional properties such as antibacterial activity, UV blocking and fire resistance which suitable for use in biomedical, industrial and defence fields [66]. Recently, another study was conducted to investigate the multifunctional properties of TiO 2 nanoparticles, which were synthesized using titanium tetraisopropoxide as the precursor in the presence of polycarboxylic acid and sodium hypophosphite as catalyst [67].…”
Section: Multifunctionalmentioning
confidence: 98%
See 1 more Smart Citation
“…The study concluded that the hybrid TiO 2 /SiO 2 nanoparticlecoated fabrics show improved multifunctional properties such as antibacterial activity, UV blocking and fire resistance which suitable for use in biomedical, industrial and defence fields [66]. Recently, another study was conducted to investigate the multifunctional properties of TiO 2 nanoparticles, which were synthesized using titanium tetraisopropoxide as the precursor in the presence of polycarboxylic acid and sodium hypophosphite as catalyst [67].…”
Section: Multifunctionalmentioning
confidence: 98%
“…Dhineshbabu et al [66] have coated sol-gel anatase TiO 2 nanoparticles and also TiO 2 nanoparticles bind with silica (SiO 2 ) on cotton fabrics by pad-dry-cure method. The study concluded that the hybrid TiO 2 /SiO 2 nanoparticlecoated fabrics show improved multifunctional properties such as antibacterial activity, UV blocking and fire resistance which suitable for use in biomedical, industrial and defence fields [66].…”
Section: Multifunctionalmentioning
confidence: 99%
“…UV transmission spectra (Lambda 35; Perkin Elmer, USA) were used to test the UV blocking property of the herbal nanocomposites coated fabrics with the wavelength region from 280 to 400 nm as reported from our previous studies [39].…”
Section: Uv Protection On Cotton Fabricsmentioning
confidence: 99%
“…Dhineshbabu et al [47] studied the UV-protection, antibacterial, and flame retardancy properties of cotton fabric treated with colloidal sols containing TEOS as precursor and polyethylene glycol (PEG) as stabilizer and TiO 2 nanoparticles produced by sol-gel process. They found that UPF values of the fabric samples were greater than 50 UPF corresponding to excellent UV protection after even 10 washing cycles.…”
Section: Uv Protection Self-cleaning and Soil Repellency (Photocatamentioning
confidence: 99%
“…Thus, their burning performance improved after the treatment and nearly 70% of this performance was preserved after 10 washing cycles. The study revealed that the fabric samples had good antibacterial activity against Staphylococcus aureus and Escherichia coli with, respectively, 18 and 15 mm diameter of inhibition zone because of the reactive oxygen species (ROS) generation mechanism of TiO 2 nanoparticles [47].…”
Section: Uv Protection Self-cleaning and Soil Repellency (Photocatamentioning
confidence: 99%